Social Capital and Collusion: The Case of Merchant Guilds - Roberta Dessí; Sheilagh Olgivie (Center for Economic Studies and ifo Institute (CESifo), 2003)
Merchant guilds have been portrayed as social networks that generated beneficial social capital by sustaining shared norms, effectively transmitting information, and successfully undertaking collective action. This social capital, it is claimed, benefited society as a whole by enabling rulers to commit to providing a secure trading environment for alien merchants. But was this really the case? We develop a new model of the emergence, rise, and eventual decline of European merchant guilds, which explores the collusive relationship between rulers and guilds, and calls into question the prevailing positive view of merchant guilds. We then confront the model's predictions with the available historical data. The empirical evidence strongly supports our model, and refutes existing theories. Our findings show that merchant guilds used their social capital for socially harmful as well as beneficial ends.
Keywords: 330; merchant guild; collusion; social capital; social networks; monopoly; taxation; rents